Weapons of War in the Future: An Analysis of M.A.K. Halliday's Semiotics on the Aljazeera.net Media Portal - Nurul Luthfiyyah; Muassomah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to analyze the construction of meaning in the discourse of Al Jazeera news entitled "Tala'ub bi-l-'admaghah wa-l-munākh wa-dh-dhakā' al-iṣṭinā'ī.. ' Ahlan bikum fī ḥurūb al-ghad" (Manipulation of the Brain, Climate, and Artificial Intelligence. Welcome to the War of the Future) – 17 November 2025, which represents the potential and evolution of modern warfare. Using a descriptive qualitative method with M.A.K. Halliday's social semiotic analysis framework, this study investigates how the media shapes public perceptions of the wars that humanity will face. The results of the analysis show that the field of discourse focuses on five main issues: the new phase of technology warfare, the cost efficiency of drone and satellite technology, Cognitive Warfare (brain fog), global trade inhibition, and Climate Engineering. The tenor of the discourse cited includes four speakers, namely anonymous officials, Stevan Audrand, Jerome Henry, and Olivier Blazy, who reinforce the authority of the narrative. In addition, the mode of discourse is used effectively through four visuals that clarify the news narrative. Overall, the study concludes that Al Jazeera not only provides information about the future forecasts of war, but also plays an important role in shaping public awareness of the continuation of global conflicts and promoting the value of military technological advances through a semiotic approach, confirming that warfare has transformed into the realm of artificial intelligence and environmental manipulation.